2021
DOI: 10.3390/s21186239
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Assessment of Delamination Using Scarce Raw Structural Vibration and Transfer Learning

Abstract: Deep learning has helped achieve breakthroughs in a variety of applications; however, the lack of data from faulty states hinders the development of effective and robust diagnostic strategies using deep learning models. This work introduces a transfer learning framework for the autonomous detection, isolation, and quantification of delamination in laminated composites based on scarce low-frequency structural vibration data. Limited response data from an electromechanically coupled simulation model and from exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 51 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The presence of a defect in laminated composites, such as delamination, affects the local stiffness/ damping, and can be simulated by inserting Teflon film between the plies of the structure to avoid localized regions between plies sticking during the curing process. 53 Another option is to alter the local properties (stiffness/damping) through the addition of local masses. 54 In the current study, the latter was employed, where the local defect was simulated via industrial adhesive putty glued to the surface of the plate at the location shown in Figure 2.…”
Section: Description Of Experimental Datamentioning
confidence: 99%
“…The presence of a defect in laminated composites, such as delamination, affects the local stiffness/ damping, and can be simulated by inserting Teflon film between the plies of the structure to avoid localized regions between plies sticking during the curing process. 53 Another option is to alter the local properties (stiffness/damping) through the addition of local masses. 54 In the current study, the latter was employed, where the local defect was simulated via industrial adhesive putty glued to the surface of the plate at the location shown in Figure 2.…”
Section: Description Of Experimental Datamentioning
confidence: 99%
“…A fault is an undesirable deviation from the normal state of a system's characteristic, property, or parameter [36,37]. The fault can be categorized into sensor, actuator, and component-level faults [38].…”
Section: Sensor Malfunctioning In Avsmentioning
confidence: 99%
“…Prognostic health monitoring is a mechanism of preventive measures to deliver comprehensive and tailored solutions for the industrial health system, management and prediction. 1,2 In civil engineering, structural health monitoring (SHM) systems are often applied to largescale civil infrastructures, especially large span bridges, to measure environmental factors, external loads and structural responses. [3][4][5] Based on measurements from SHM systems, anomaly detection for large span bridges has been broadly studied all over the world within recent decades.…”
Section: Introductionmentioning
confidence: 99%